E-content module for Chemistry Massive Open Online Course (MOOC): Development and students' perceptions - Siti Nurshuhada Mohd Hamid; Tien Tien Lee; Hafsah Taha; Nurulsaidah Abdul Rahim; Aisyah Mohamad Sharif (OmniaScience, 2021)
This study aimed to develop an e-content module for Chemistry Massive Open Online Course (MOOC). It examined the validity, reliability and student's perceptions on content, usability, design and effectiveness of the module. This is a design and development study and the e-content module was developed based on ADDIE instructional design model. Collaborative learning, Connectivism theory and Interaction Equivalency Theorem are the pillars for the module development. The content validity of the module was estimated by three experts using content validity evaluation form. Questionnaires were distributed to the students in order to determine the reliability (n = 23) and students' perceptions on the module (n = 129). Findings revealed the e-content module has high content validity (CVI = 1.00) and good reliability index (α = 0.94). The mean scores for students' perception on module content (M = 3.66, SD = 0.55), usability (M = 3.43, SD = 0.56), design (M = 3.41, SD = 0.59) and effectiveness (M = 3.47, SD = 0.56) constructs were high. This e-content module in Chemistry MOOC is hoped to be a good and useful online resource for both students and lecturers in the teaching and learning of Chemistry in higher education institution.